A signal, from human mtDNA, of postglacial recolonization in Europe - Torroni A; Bandelt HJ; Macaulay V; Richards M; Cruciani F; Rengo C; Martinez-Cabrera V; Villems R; Kivisild T; Metspalu E; Parik JR; Tolk HV; et al. (The American Journal of Human Genetics, 2001)
Mitochondrial HVS-I sequences from 10,365 subjects belonging to 56 populations/geographical regions of western Eurasia and northern Africa were first surveyed for the presence of the T→C transition at nucleotide position 16298, a mutation which has previously been shown to characterize haplogroup V mtDNAs. All mtDNAs with this mutation were then screened for a number of diagnostic RFLP sites, revealing two major subsets of mtDNAs. One is haplogroup V proper, and the other has been termed "pre*V," since it predates V phylogenetically. The rather uncommon pre*V tends to be scattered throughout Europe (and northwestern Africa), whereas V attains two peaks of frequency: one situated in southwestern Europe and one in the Saami of northern Scandinavia. Geographical distributions and ages support the scenario that pre*V originated in Europe before the Last Glacial Maximum (LGM), whereas the more recently derived haplogroup V arose in a southwestern European refugium soon after the LGM. The arrival of V in eastern/central Europe, however, occurred much later, possibly with (post-)Neolithic contacts. The distribution of haplogroup V mtDNAs in modern European populations would thus, at least in part, reflect the pattern of postglacial human recolonization from that refugium, affecting even the Saami. Overall, the present study shows that the dissection of mtDNA variation into small and well-defined evolutionary units is an essential step in the identification of spatial frequency patterns. Mass screening of a few markers identified using complete mtDNA sequences promises to be an efficient strategy for inferring features of human prehistory.